Gut microbiota-mediated programmed cell death in colorectal cancer: implications for precision medicine - Wei Liu; Wei Zhang (Oncologie, 2026)
Abstract Colorectal cancer (CRC) remains a major global health burden, with marked interindividual variability in disease progression and therapeutic response. Emerging evidence suggests that the gut microbiota shapes CRC biology not only through inflammation and metabolism, but also by regulating programmed cell death (PCD) pathways that may influence tumor cell fate and treatment sensitivity. This review summarizes recent advances in microbiota-mediated regulation of major PCD modalities relevant to CRC, including apoptosis, pyroptosis, ferroptosis, autophagy, and emerging forms of regulated cell death. We discuss how microbial species, microbial metabolites, and microbiota-derived signals influence these processes through immune modulation, metabolic reprogramming, epithelial barrier regulation, and canonical signaling pathways. Importantly, the available evidence is predominantly preclinical, consisting largely of in vitro and animal studies, with limited clinical or correlative data. For several mechanisms, CRC-specific evidence remains incomplete, and relevant insights are partly extrapolated from intestinal inflammatory conditions or non-CRC tumor models. We therefore examine the potential, rather than established, translational implications of microbiota–PCD interactions for biomarker development, therapeutic stratification, and microbiome-targeted interventions. We also review microbiota-based strategies, including probiotics, prebiotics, synbiotics, postbiotics, fecal microbiota transplantation, dietary interventions, and other microbiome-targeted approaches, while highlighting challenges related to causality, patient heterogeneity, safety, standardization, and clinical validation. Overall, the microbiota–PCD axis provides a mechanistic framework for future CRC-specific investigation, but its clinical utility requires validation in well-designed prospective studies and interventional trials.